Zfhx3 modulates retinal sensitivity and circadian responses to light - Hughes, S; Edwards, JK; Wilcox, AG; Pothecary, CA; Barnard, AR; Joynson, R; Joynson, G; Hankins, MW; Peirson, SN; Banks, G; Nolan, PM (Federation of American Societies for Experimental Biology, 2021)
Mutations in transcription factors often exhibit pleiotropic effects related to their complex expression patterns and multiple regulatory targets. One such mutation in the zinc finger homeobox 3 (ZFHX3) transcription factor, short circuit (Sci, Zfhx3Sci/+), is associated with significant circadian deficits in mice. However, given evidence of its retinal expression, we set out to establish the effects of the mutation on retinal function using molecular, cellular, behavioral and electrophysiological measures. Immunohistochemistry confirms the expression of ZFHX3 in multiple retinal cell types, including GABAergic amacrine cells and retinal ganglion cells including intrinsically photosensitive retinal ganglion cells (ipRGCs). Zfhx3Sci/+mutants display reduced light responsiveness in locomotor activity and circadian entrainment, relatively normal electroretinogram and optomotor responses but exhibit an unexpected pupillary reflex phenotype with markedly increased sensitivity. Furthermore, multiple electrode array recordings of Zfhx3Sci/+retina show an increased sensitivity of ipRGC light responses.